2018
DOI: 10.1007/978-1-4939-7558-7_18
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Amyloid Plaques and Neurofibrillary Tangles from Archived Alzheimer’s Disease Tissue Using Laser-Capture Microdissection for Downstream Proteomics

Abstract: Here, we describe a new method that allows localized proteomics of amyloid plaques and neurofibrillary tangles (NFTs), which are the two pathological hallmarks of Alzheimer’s disease (AD). Amyloid plaques and NFTs are visualized using immunohistochemistry and microdissected from archived, formalin-fixed paraffin-embedded (FFPE) human tissue samples using laser-capture microdissection. The majority of human tissue specimens are FFPE; hence the use of this type of tissue is a particular advantage of this techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…With the use of laser capture microscopy and proteomics techniques, analyses of micro-dissected regions are feasible and could identify key neuroinflammatory factors associated with AD that are not represented when larger dissected pieces of brain tissue are analyzed. The feasibility of this approach has been demonstrated in proteomic analyses of micro-dissected plaques and tangles from AD brains [49,50]. microglial P2RY12 with ticagrelor, an antagonist, reduced ischemic damage by microglia by reducing their migration to sites of injury [47].…”
Section: Discussionmentioning
confidence: 99%
“…With the use of laser capture microscopy and proteomics techniques, analyses of micro-dissected regions are feasible and could identify key neuroinflammatory factors associated with AD that are not represented when larger dissected pieces of brain tissue are analyzed. The feasibility of this approach has been demonstrated in proteomic analyses of micro-dissected plaques and tangles from AD brains [49,50]. microglial P2RY12 with ticagrelor, an antagonist, reduced ischemic damage by microglia by reducing their migration to sites of injury [47].…”
Section: Discussionmentioning
confidence: 99%
“…We sampled brain tissue from formalin-fixed paraffin embedded (FFPE) blocks of hippocampus or superior frontal gyrus collected and processed for autopsy neuropathology. LCM was performed using our published protocol [31][32][33]. Briefly, 8µm-thick FFPE sections containing hippocampus or frontal superior gyrus were collected onto LCM PET Frame Slides (Leica).…”
Section: Laser-capture Microdissection (Lcm)mentioning
confidence: 99%
“…The samples were subsequently digested with 300ng of sequencing grade modified trypsin (Promega) overnight at RT with gentle shaking. After digestion samples were acidified with trifluoroacetic acid to a pH of 2 and peptides were desalted using POROS R2 C18 beads as previously described [31][32][33]. The samples were resuspended in 0.5% acetic acid and stored at -80C until further analysis.…”
Section: Label-free Quantitative Mass Spectrometry (Ms) Proteomicsmentioning
confidence: 99%
“…This study is an example of the powerful and informative nature of unbiased localized proteomics studies, which permit the discovery of novel disease related proteins present within neuropathological features through unbiased analysis [12][13][14][15]. It is important to recognize that SCRN1 was only brought to our attention as a novel AD associated protein because of the localized nature of our original proteomics study that identified SCRN1 in dystrophic neurites in amyloid plaques [12].…”
Section: Discussionmentioning
confidence: 99%